2018
DOI: 10.32007/jfacmedbagdad.59471
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF-α 308 polymorphism with diabetes mellitus type 2

Abstract: Back ground: The association between tumors necrosis factor-alpha (TNF-á)308 polymorphism and type 2 diabetes mellitus (T2DM) remains controversial .The variation in ethnicity and life style play important role in these conflicting results.Objective: To investigate association of TNF-á 308 polymorphism with T2DM,TNF level and body mass index in these patients.Patients and methods: The current case control study included fifty patients with T2DM in addition to twenty five healthy controls. The fasting blood sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Additionally, the increased apelin levels among rats indicated that it had a powerful anti-type-2 diabetes activities and acted as insulin-sensitization agents [34,35]. The present study in agreement with result done by Hachim et al, who Stated Association of TNF-α 308 polymorphism with diabetes mellitus type 2 [36], another study also demonstrate by Liu et al, who said that Meta-analysis of 19 studies shows that elevated TNF-levels are strongly associated with an increased risk of developing Type 2 Diabetes Mellitus (T2DM) [37].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the increased apelin levels among rats indicated that it had a powerful anti-type-2 diabetes activities and acted as insulin-sensitization agents [34,35]. The present study in agreement with result done by Hachim et al, who Stated Association of TNF-α 308 polymorphism with diabetes mellitus type 2 [36], another study also demonstrate by Liu et al, who said that Meta-analysis of 19 studies shows that elevated TNF-levels are strongly associated with an increased risk of developing Type 2 Diabetes Mellitus (T2DM) [37].…”
Section: Discussionsupporting
confidence: 93%